Stimulating debate: ethics in a multidisciplinary functional neurosurgery committee. Issue 2 (30th January 2006) - Ford, Paul J; Kubu, Cynthia S
Abstract : Multidisciplinary healthcare committees meet regularly to discuss patients' candidacy for emerging functional neurosurgical procedures, such as Deep Brain Stimulation (DBS). Through debate and discussion around the surgical candidacy of particular patients, functional neurosurgery programs begin to mold practice and policy supported both by scientific evidence and clear value choices. These neurosurgical decisions have special considerations not found in non-neurologic committees. The professional time used to resolve these conflicts provides opportunities for the emergence of careful, ethical practices simultaneous with the expansion of therapy applications